A 2100MPa grade hot-rolled wire rod for bridge cables and a manufacturing method thereof
Through high Si-Mn chemical composition and online molten salt soxunitization regulation technology, the problem of deteriorating tissue control in hot-rolled strips for 2100MPa-level bridge cables is solved, and the strong plastic matching and stable production of the strips are achieved, reducing the risk of wire breakage.
Patent Information
- Application Number
- CN202411856803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The hot-rolled strips for 2100MPa-grade bridge cables are difficult to control the deteriorating structure of mesh carbides, martensites and other materials during the production process, resulting in a high risk of wire breaking, which limits the rapid application and promotion of bridge cables.
Using high Si-Mn chemical composition design and combined with online molten salt sornatic regulation technology, the control strip quickly enters the sornatic phase area from the high-temperature austenite state, forming a tissue dominated by fine sheet spacing sornaite, reducing the difficulty of isothermal stress removal, and promoting further toughening of the tissue through the rollers.
The formation of mesh carbides and martensite is effectively avoided, the strengthening effect of carbon elements is improved, the strong plastic matching of the strips is enhanced, the risk of broken wire is reduced, and the stable production of 2100MPa-level bridge cables is achieved.
Smart Images

Figure CN119303991B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and in particular relates to a 2100MPa-grade hot-rolled wire rod for bridge cables and a manufacturing method thereof. Background Art
[0002] As one of the typical representatives of ultra-high strength bridge cables, 2100MPa-grade bridge cables are made of hot-rolled wire rods as raw materials, and are processed through processes such as wire rod unwinding, pickling, multi-pass deep wire drawing, hot-dip galvanizing, and twisting. Therefore, the performance of the hot-rolled wire rod parent material is directly related to the tensile strength, drawing performance, number of twistings, fatigue life, etc. of the bridge cable steel wire. High-carbon pearlite steel has excellent drawing performance and is often used in the field of large drawing volume and high strength. However, as the level of bridge cables increases, the difficulty of manufacturing hot-rolled wire rod parent materials continues to rise. At present, most of the wire rods used for high-strength bridge cable drawing adopt a high-carbon component system, combined with the Stelmore air-cooling line after spinning to control the wire rod structure and performance. It is precisely because of the low cooling rate and large fluctuation of the cooling rate of the Stelmore air-cooling line that the network carbide, martensite and other deteriorated structures of the hot-rolled wire rod for 2100MPa-grade bridge cables are extremely difficult to control during the production process, resulting in a high risk of wire breakage during the wire drawing process, limiting the rapid application and promotion of 2100MPa-grade bridge cables. Therefore, it is urgently needed to develop a 2100MPa-grade bridge cable wire rod with low cost, matching strength and plasticity, and stable production, and its manufacturing method to meet the development of the steel industry and market demand.
[0003] The technical difficulties that currently limit the performance and production of 2100MPa bridge cable wire rods are mainly:
[0004] 1. With the development of ultra-high strengthening of parent materials, in order to improve the strength of wire rods and reduce the strength loss of wire rods in the subsequent hot-dip galvanizing process, high-strength wire rods for bridge cables will adopt a high-carbon and high-silicon component system, and further combine trace strengthening elements such as Nb, V, Ti, B, etc. to refine grains or precipitate strengthening. For example, CN107587071B discloses a steel for bridge cables with a tensile strength ≥2100MPa and a production method, which adopts a C-Si-Mn-Cr-Nb-Al-B-Zr component system, combined with Stelmor strong wind cooling to room temperature after spinning to obtain wire rods, but on the one hand, the high C element will aggravate the steel Carbon segregation during the solidification process of the billet. During the cooling process, due to the limitation of the maximum cooling capacity of air cooling, the wire rod passes through the precipitation temperature range of secondary cementite for a long time. The cementite precipitated along the grain boundary will form a higher level of network carbide, which will seriously affect the uniformity of the wire rod structure and the plasticity and toughness properties, and aggravate the risk of wire drawing and torsion fracture. On the other hand, the addition of expensive trace elements such as Nb, B, and Zr will increase the material cost. With the purpose of reducing material costs, the addition of trace elements will lose the fine grain strengthening effect, affect the strength and toughness of the wire rod, and is not conducive to drawing to achieve the 2100MPa bridge cable performance level and meet the torsion performance.
[0005] Second, in order to minimize the adverse effects of network carbides, high-strength bridge cable wire rods will use strong wind cooling before phase transformation or further combine with water mist or water bath controlled cooling. For example, the hot-rolled wire rods and production methods for galvanized steel wires for bridge cables of 2100MPa and above disclosed in patent CN116145036A adopt C-Si-Mn-Cr-Al-V-Nb-Ti composition design, combined with thermal relaxation after spinning and water bath cooling to obtain troostite structure wire rods. However, in order to obtain refined pearlite, i.e. troostite structure, which is beneficial for drawing, in the low-temperature phase transformation range, the content of alloy components such as Si, Mn, and Cr in the wire rods is relatively high, which also aggravates the segregation of alloy components and the influence of hardenability. Under the action of strong wind cooling, the wind speed and wind temperature fluctuations increase. The temperature difference between the windward side and the leeward side of the wire rod will further increase. When the wire rod diameter is larger, the temperature difference from the upper edge to the core of the same circle section will further increase. Under the action of water mist or water bath, a large number of bubbles will be generated in the heat exchange process and attached to the surface of the wire rod, affecting heat transfer, so that the cooling rate fluctuation of the wire rod will further increase, and the distribution of the phase change structure will become uneven. In addition, due to the influence of component segregation and hardenability, some overcooled positions are more likely to form hard and brittle low-temperature structures such as bainite or martensite with high distortion and poor drawing performance, which will seriously affect the plasticity and toughness of the wire rod, increase the fluctuation of the mechanical properties of the wire rod, and further affect the wire drawing and torsional performance of the wire rod. In the subsequent large-scale drawing processing, wire breakage is very likely to occur, and even cause brittle fracture during the coiling or transportation of the wire rod, which is not conducive to stable production.
[0006] 3. In order to improve the strength of wire rod and obtain appropriate drawing performance, the wire rod for high-strength bridge cable adopts hardenability components such as Mn, Cr, B and trace elements such as Nb, V, Ti, combined with low-temperature rolling to refine grains, and reduce the air cooling intensity during the phase transformation process to extend the phase transformation time and obtain more troostite structure at a lower temperature. However, on the one hand, the minimum cooling control capacity of air cooling and water cooling is limited, and the supercooling from spinning to phase transformation temperature is low. The high Si content prolongs the phase transformation incubation time of the wire rod structure, which will limit the rapid phase transformation of troostite. The proportion of soft phase ferrite in the structure increases, which will affect the strength of the wire rod. On the other hand, the high alloy content will limit the diffusion activity of carbon elements. With the increase of carbon content and the increase of cementite lamella thickness, the wire rod passes through the high-temperature phase transformation temperature range for a short time. After the phase transformation incubation, it is in a low temperature state, which will leave large stress and dislocation density in the structure, making the wire rod ultimately insufficient in plasticity, and the plasticity loss is faster in the subsequent deep drawing process, which will cause the risk of wire breakage. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a 2100MPa grade hot-rolled wire rod for bridge cables and a manufacturing method thereof, which can effectively control deteriorated structures such as network carbides and martensite, realize wire rod structure regulation, strength-plasticity matching and stable production, is suitable for the manufacture of 2100MPa grade bridge cables, and is beneficial to reducing the risk of wire breakage.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for manufacturing a 2100MPa grade hot-rolled wire rod for bridge cables, the manufacturing method comprising:
[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, and the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.88%~0.92%, Si: 1.10%~1.30%, Mn: 1.00%~1.20%, Cr: 0.47%~0.67%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥955°C, it is subjected to an online molten salt sorbitization control treatment, so that the wire rod is cooled at a cooling rate of ≥36°C / s, enters the sorbitan phase region from the austenite state, promotes the sorbitan phase transformation and isothermal treatment to relieve stress, and finally is slowly cooled by a roller to produce a hot-rolled wire rod with a microstructure including tempered sorbitan with a volume percentage of ≥95%, and the rest is a mixed structure composed of ferrite and fused sorbitan.
[0011] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:
[0012] (1) Carbon: As an effective carbide strengthening element and austenite forming element, C is cheaper than other alloying elements. As the carbon content increases, it is beneficial to form more troostite structure in the wire rod during the online molten salt troostitizing control treatment, thereby improving the tensile strength of the material. However, as the carbon content in hypereutectoid steel increases, the tendency of central carbon segregation during the solidification of the billet increases, the tendency of decarburization and precipitation of network cementite increases, the toughness and plasticity of the material deteriorates, and the cementite layer becomes thicker, which increases the difficulty of isothermal stress relief and leads to unqualified shrinkage and torsion indicators. Therefore, in order to take into account the high strength requirements of 2100MPa-level bridge cables and reduce the difficulty of network carbide control and isothermal stress relief, the mass percentage of C is controlled to be 0.88%~0.92%.
[0013] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. Si dissolved in the ferrite phase will play a role in strengthening the material. At the same time, it can inhibit the coarsening of cementite during the online molten salt troostitizing treatment, so that a troostite structure with fine interlamellar spacing can be obtained. It is also beneficial to reduce the difficulty of isothermal melting and stress relief of cementite. After the wire rod is drawn into steel wire, it is beneficial to reduce the strength loss in the subsequent hot-dip galvanizing process. However, too high a silicon content will make the steel easier to decarburize when heated at high temperature, prolong the transformation time during the phase change process, and reduce the toughness of the steel. Therefore, the Si content is appropriately increased, and the mass percentage of Si is controlled to be 1.10%~1.30%.
[0014] (3) Manganese: Mn can be added as a deoxidizer during the smelting process, mainly playing a role in solid solution strengthening, while increasing the hardenability of the wire rod and the stability of austenite, which is beneficial to reducing the phase transformation temperature, and thus is beneficial to regulating the molten salt temperature and controlling the network carbide by rapid cooling of the molten salt. It is also beneficial to promote the rapid nucleation of the sorbite structure with fine lamellar spacing during the online molten salt sorbitization control treatment, which can improve the matrix strength. However, when the Mn content is too high, it will increase the steel's overheating sensitivity, grain coarsening and composition segregation tendency, and increase the risk of martensite precipitation in the core of the wire rod. At the same time, it will reduce the diffusion activity of carbon, increase the difficulty of isothermal stress relief softening, and then lose the plasticity of the wire rod. Therefore, in order to take into account the high strength of the hot-rolled wire rod and reduce the difficulty of controlling the uniformity of the structure, the Mn content is appropriately increased, and the mass percentage of Mn is controlled to be 1.00%~1.20%.
[0015] (4) Chromium: Cr is a strong carbide-forming element in high carbon steel. It can play a role in solid solution strengthening and improving hardenability. It is beneficial to reduce the phase transformation temperature and refine the spacing between cementite sheets. It is beneficial to improve the drawing performance and increase the matrix strength. At the same time, it is beneficial to increase the work hardening rate of the wire rod during the wire drawing process and reduce the strength loss during the subsequent hot-dip galvanizing process of the steel wire. However, too high Cr content will aggravate the component segregation, increase the risk of low-temperature microstructure precipitation, reduce the activity of carbon in the steel, and significantly increase the difficulty of improving the plasticity of the wire rod. It is not conducive to isothermal stress relief during online molten salt sorbitization control treatment and will deteriorate the torsional performance of the steel wire. Therefore, the mass percentage of Cr is controlled to be 0.47%~0.67%.
[0016] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0017] The hot-rolled wire rod adopts a high-carbon component design of C-Si-Mn-Cr, and does not add expensive trace alloy components such as Nb, Ti, and V, which can appropriately reduce the material cost. At the same time, the Si, Mn, and Cr component ratios are appropriately adjusted to appropriately reduce the peak precipitation temperature of the sorbite, which provides favorable conditions for forming a large temperature gradient during online molten salt sorbitization, effectively controlling the precipitation of network carbides, promoting the rapid formation of a structure dominated by sorbite with fine interlamellar spacing, and reducing the difficulty of stress relief in the high-temperature isothermal zone. On this basis, the manufacturing method adopts a higher spinning temperature, which can avoid the precipitation of cementite and the formation of network carbides in the spinning stage caused by too low spinning temperature, and at the same time provide favorable conditions for promoting the nucleation of sorbite. After spinning, the molten salt treatment is directly performed for online molten salt sorbitization regulation:
[0018] First, compared with the Stelmore air-cooled line, which has a limited maximum cooling capacity and is difficult to control network carbides and causes cementite lamellae coarsening, on the one hand, online molten salt sorbitization regulates the wire rod from the high-temperature austenite state to the sorbite phase region, and can use the high heat exchange capacity of molten salt to significantly increase the cooling rate of the wire rod, so that the wire rod can quickly pass through the secondary cementite precipitation temperature range of 700~800℃, thereby improving the segregation effect caused by high carbon content and avoiding the formation of network carbide structure that is unfavorable to the uniformity and plasticity of the organization; on the other hand, the temperature gradient from the spinning temperature to the sorbite phase region is large, and a large degree of supercooling can be formed under rapid cooling. Combined with Si to inhibit the coarsening of cementite, it can promote the rapid phase transformation of the austenite structure in the wire rod structure to form a structure dominated by sorbite with fine lamellar spacing, reduce the proportion of ferrite, improve the matrix strength, and reduce the difficulty of isothermal stress relief.
[0019] 2. Compared with the unstable cooling rate control of the Stelmore air-cooled line or water-cooled controlled cooling, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for uniform heat transfer, and there is no temperature difference problem between the windward side and the leeward side, and a large number of bubbles will not be formed on the surface of the wire rod to affect the heat transfer as in water cooling. On the one hand, after the wire rod is sorbitized online with molten salt, it can maintain the same temperature as the molten salt, and undergo phase transformation in the sorbitide phase region, avoiding overcooling of some positions and producing abnormal martensitic structure that is unfavorable for drawing, improving the segregation caused by the addition of Mn and Cr hardenability elements and the precipitation of low-temperature abnormal structure, making the wire rod production more stable. On the other hand, the high heat exchange capacity of the molten salt also makes the temperature difference from the edge to the core of the same cross-section of the wire rod with larger specifications further reduced, which can promote uniform phase transformation of the wire rod, reduce the distribution difference of the sorbitide content on the same cross-section, further improve the uniformity of the organization, reduce the fluctuation of the mechanical properties of the wire rod, and reduce the risk of wire breakage during the wire drawing process.
[0020] 3. Compared with the Stelmore air cooling line or water cooling controlled cooling, which has limited minimum cooling capacity or continuous cooling control, limiting the sorbite phase transformation and softening, the online molten salt sorbitization control can keep the wire rod consistent with the molten salt temperature, and carry out a longer high-temperature isothermal treatment in the sorbite phase region instead of continuous cooling. On the one hand, it can maintain the sorbite peak precipitation temperature, promote the full transformation of austenite structure to fine pearlite structure, i.e. sorbite structure, improve the adverse effect of adding Si on phase transformation inoculation, reduce the proportion of soft phase ferrite, and improve the matrix. Strength, to make up for the strength loss caused by not adding expensive trace alloy elements. On the other hand, it can control the wire rod to relieve stress in the high temperature isothermal zone, reduce the dislocation density of troostite, transform it into toughened tempered troostite structure, promote the melting of cementite lamellae into melting troostite structure, and improve the strength and plasticity matching of the wire rod. In the subsequent roller slow cooling process, it can prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, improve the softening effect of the wire rod, and thus achieve wire rod structure regulation and stable production.
[0021] Since the content of carbon and alloy elements in the wire rod component system is relatively high, selecting a higher soaking temperature of the heating furnace before rolling can promote uniform diffusion of the wire rod components and appropriately reduce component segregation. In a preferred embodiment, before rolling, the soaking temperature of the heating furnace is controlled to be 1150~1200℃, and the time in the furnace is ≥180min.
[0022] Due to the high spinning temperature, a higher rolling temperature can be selected to reduce the deformation resistance of the steel billet and the wear on the rolling line, promote the rapid rolling of the wire rod, select a suitable rolling temperature and final rolling pressure drop, promote dynamic recrystallization during the final rolling process, and refine the grains. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1120~1160℃, the final rolling temperature is 980~1020℃, and the final rolling reduction is 22%~27%.
[0023] The molten salt temperature of the online molten salt troostitizing regulation treatment is in the troostite phase region temperature. The lower the molten salt temperature, the greater the supercooling can be formed, which is beneficial to promoting the transformation of austenite to troostite and controlling the refinement of cementite lamellae, and can improve the matrix strength. However, if the molten salt temperature is too low, it is not conducive to controlling the rapid isothermal stress relief of the wire rod, which will cause plasticity loss, and if the temperature is too low, it may enter the bainite phase region and produce hard and brittle bainite abnormal structure; on the contrary, the higher the molten salt temperature, the more thermal power can be provided, which is beneficial to promoting the toughening of the wire rod structure and improving the softening effect. However, if the molten salt temperature is too high, it is not conducive to controlling the network carbide and promoting the troostite phase transformation of the fine lamellae spacing, which will cause strength loss; the longer the treatment time, the more austenite can be promoted to fully transform to troostite. Change, reduce the ferrite content, and at the same time enable the wire rod to be stress-relieved in a longer high-temperature isothermal zone, thereby regulating the strength and plasticity of the wire rod. However, if the treatment time is too long, the melting of sorbite will increase, which will bring a certain strength loss, and the precipitation and coarsening of Cr at high temperature for a long time is not conducive to the strength and plasticity. On the contrary, the shorter the treatment time, the lower the toughening and softening effect of the wire rod structure. However, if the treatment time is too short, the high stress of the wire rod structure will lead to insufficient plasticity, and even the wire rod will not be fully transformed into sorbite, which will bring strength loss. Therefore, the molten salt temperature and treatment time can be further controlled to control the wire rod structure and the stress relief effect. In a preferred embodiment, the molten salt temperature of the online molten salt sorbitization treatment is 490~525℃, and the treatment time is 170~360s.
[0024] The online molten salt sorbitization regulation treatment can be divided into a front-end treatment and a back-end treatment. Since the temperature difference of the wire rod from the high-temperature austenite state to the sorbite phase transformation temperature is large, a larger molten salt circulation volume is selected in the front-end treatment to control the temperature rise of the molten salt and promote the rapid cooling of the wire rod. The wire rod can be consistent with the molten salt temperature after rapid heat exchange with the molten salt. The difficulty of controlling the temperature rise of the molten salt is reduced under isothermal treatment. The molten salt circulation volume is appropriately reduced in the back-end treatment, which can appropriately reduce the production energy consumption while accurately controlling the temperature. In a preferred embodiment, the molten salt circulation volume of the front-end treatment is greater than the molten salt circulation volume of the back-end treatment, and the processing time of the front-end treatment is greater than the processing time of the back-end treatment; in a preferred embodiment, the molten salt circulation volume of the front-end treatment is 350~420t / h, the molten salt temperature rise is ≤10°C, and the processing time is 160~260s; in a preferred embodiment, the molten salt circulation volume of the back-end treatment is 150~250t / h, the molten salt temperature rise is ≤5°C, and the processing time is 10~100s.
[0025] Since the wire rod can maintain a high temperature state of 490~525℃ after online molten salt sorbitization regulation, a lower cooling rate is selected to control the slow cooling of the wire rod, which can continue the stress relief effect in the high temperature isothermal range and avoid stress increase caused by too fast cooling. It can promote further toughening and softening of the wire rod structure and enhance the plasticity of the wire rod. In a preferred embodiment, the roller slow cooling controls the wire rod to slowly cool to below 300℃ at a cooling rate of 0.1~0.3℃ / s.
[0026] A 2100MPa grade hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any one of the above-mentioned methods for manufacturing the 2100MPa grade hot-rolled wire rod for bridge cables.
[0027] The above-mentioned hot-rolled wire rod is designed with high Si-Mn chemical composition. Under the control of high-temperature spinning and online molten salt sorbitization, a structure dominated by tempered sorbite is obtained, which can effectively control the deterioration of network carbides, martensite and other deteriorated structures. The interlamellar spacing of sorbite is finer than that of pearlite, and the strength and drawing hardening ability are higher than those of pearlite structure, and the plasticity is better than that of bainite structure. The matrix strength can be improved by refining the lamellae, increasing the content of sorbite structure, and reducing the proportion of ferrite, so as to make up for the strength loss caused by not adding elements such as V, Ti, Nb, and B. At the same time, after the sorbite is isothermal stress relief, the dislocation density is further reduced, the sorbite is transformed into toughened tempered sorbite, and the cementite lamella is melted and transformed into melted sorbite, which can improve the plasticity of the wire rod and match it with high strength, thereby obtaining a strong and tough organizational state, which is beneficial to improve the adverse effects of increasing Si and Mn content on plastic and toughness properties, and is suitable for the manufacture of 2100MPa-level bridge cables, meeting the requirements of drawing, hot-dip galvanizing and torsion performance.
[0028] The higher the proportion of the tempered troostite, the better the strength and plasticity of the wire rod, and the smaller the interlamellar spacing of the tempered troostite, the higher the matrix strength. However, the interlamellar spacing of the tempered troostite is too fine, and the required molten salt temperature is too low, which is not conducive to controlling the rapid stress relief of the wire rod in the high-temperature isothermal zone. Therefore, in a preferred embodiment, the interlamellar spacing of the tempered troostite is 65~115mm.
[0029] In a preferred embodiment, the network carbide grade of the hot-rolled wire rod is grade 0, which can effectively improve the deterioration effect of the network carbide on the uniformity and plasticity of the structure and enhance the strengthening effect of the carbon element.
[0030] Since the abnormal network carbides and martensite structures of the wire rod are effectively controlled and the tempered troostite on the wire rod cross section is evenly distributed, the uniformity of the structure can be further improved, the fluctuation of the mechanical properties of the wire rod can be reduced, and the risk of wire breakage during drawing can be reduced, and the torsional performance can be improved. In a preferred embodiment, the mechanical property difference of the hot-rolled wire rod is less than 60MPa.
[0031] In a preferred embodiment, the diameter of the hot-rolled wire rod is 12.0~15.5mm, the tensile strength is 1500~1540MPa, and the cross-sectional shrinkage rate is 37%~42%. The wire rod has a high tensile strength, so that the wire rod can be further strengthened after drawing, reducing the strength loss during the hot-dip galvanizing process, and reaching the 2100MPa bridge cable performance level. The wire rod has a high cross-sectional shrinkage rate and exhibits high plasticity, which can reduce the risk of cracking during drawing and torsion, and improve the production stability of 2100MPa bridge cable manufacturing.
[0032] Compared with the prior art, the beneficial effects of the present invention are at least:
[0033] (1) In view of the low cooling rate and large cooling rate fluctuation of the existing Stelmor air-cooled line, the network carbide, martensite and other deteriorated structures are extremely difficult to control during the production process of the hot-rolled wire rod for 2100MPa bridge cables, and the high risk of wire breakage during the wire drawing process. The manufacturing method of the present invention adopts a high Si-Mn chemical composition design combined with an online molten salt sorbitization control technology to control the wire rod to quickly enter the sorbitide phase region from the high-temperature austenite state to form a structure dominated by sorbitide with fine lamellar spacing. This can effectively avoid the risk of abnormal structures such as network carbides and martensite produced by the C element, enhance the strengthening effect of the carbon element, and at the same time control the wire rod to enter the high-temperature isothermal zone to relieve stress. Finally, the wire rod is slowly cooled through a roller to promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod, achieving wire rod structure control, strength-plasticity matching and stable production, and having good industrial adaptability.
[0034] (2) In view of the current situation that the deterioration structure of the existing 2100MPa grade hot-rolled wire rod for bridge cables is difficult to control and contains a large number of micro-alloying elements, the hot-rolled wire rod of the present invention adopts a high Si-Mn chemical composition, which can save precious alloying elements such as V, Ti, Nb, and B, and appropriately reduce material costs. At the same time, the microstructure type is a mixed structure composed of tempered troostite, ferrite, and melt troostite. The matrix strength can be improved by refining the lamellar layers, increasing the troostite content, and reducing the ferrite ratio. The structure toughening is achieved by regulating the stress relief of the structure to transform it into tempered troostite and melt troostite, thereby improving the strength-plasticity matching of the wire rod, effectively controlling the deterioration structures such as network carbides and martensite, and achieving a tensile strength of 1500~1540MPa and a cross-sectional shrinkage rate of 37%~42%. It is used in the manufacture of 2100MPa grade ultra-high strength bridge cables and other application fields, which is beneficial to reducing the risk of wire breakage, meeting the torsional performance requirements, reducing the strength loss during hot-dip galvanizing, and promoting the stable production of bridge cables. It has a good market application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0037] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0038] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0039] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0040] A preferred embodiment of the manufacturing method of the 2100MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.92%, Si: 1.22%, Mn: 1.00%, Cr: 0.55%, P: 0.012%, S: 0.010%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt sorbentization control treatment → roller slow cooling → coiling, specifically:
[0041] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, and reduce segregation. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 13mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process, and specifically: control the heating furnace soaking temperature to 1165°C, the furnace time to 20 0min, the initial rolling temperature is 1135℃, the final rolling temperature is 990℃, and the final rolling reduction is 25%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. A higher wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the troostite phase transformation dominated by fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 960℃.
[0042] The online molten salt sorbitization control treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region, inhibits the formation of network carbides, promotes the phase transformation of high-temperature austenite to sorbite, and forms a structure dominated by sorbite with fine lamellar spacing. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for The post-stage treatment is carried out, and the molten salt circulation volume of the post-stage treatment is appropriately reduced to reduce production energy consumption, further control the stress relief of the wire rod in the high-temperature isothermal zone, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature is 496°C, and the total treatment time is 360s, of which the molten salt circulation volume of the front-stage treatment is 380t / h, the molten salt temperature rise is ≤10°C, and the treatment time is 260s; the molten salt circulation volume of the post-stage treatment is 150t / h, the molten salt temperature rise is ≤5°C, and the treatment time is 100s.
[0043] The roller slow cooling process adopts closing the insulation cover, passing the hot air above the salt bath tank into the insulation cover, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 290°C at a cooling rate of 0.15°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain a hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.
[0044] Comparative Example 1:
[0045] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1110°C, the furnace time is 260min, the initial rolling temperature is 1085°C, the final rolling temperature is 915°C, and the spinning temperature is 890°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~6# fans at 85%, cool the wire rod to 665℃ at a cooling rate of 8.5℃ / s, and then open 7~14# fans at 25%, cool the wire rod to 290℃ at a cooling rate of 3.3℃ / s, and obtain the hot-rolled wire rod product after it comes off the line.
[0046] Comparative Example 2:
[0047] A method for manufacturing a hot-rolled wire rod, the manufacturing method differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1125°C, the furnace time is 220min, the initial rolling temperature is 1000°C, the final rolling temperature is 935°C, the spinning temperature is 905°C, and when the wire rod undergoes front-end treatment, the wire rod is cooled at a cooling rate of 34°C / s, and a hot-rolled wire rod finished product is obtained after it comes off the line. Embodiment 2:
[0048] A preferred embodiment of the manufacturing method of the 2100MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.88%, Si: 1.15%, Mn: 1.17%, Cr: 0.47%, P: 0.013%, S: 0.010%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt sorbentization control treatment → roller slow cooling → coiling, specifically:
[0049] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, and reduce segregation. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 12mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process, and specifically: control the heating furnace soaking temperature to 1150°C, and the furnace time to 21 0min, the initial rolling temperature is 1120℃, the final rolling temperature is 980℃, and the final rolling reduction is 27%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. A higher wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the troostite phase transformation dominated by fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 955℃.
[0050] The online molten salt sorbitization control treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-stage treatment, so that the wire rod is cooled at a cooling rate of 36°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region, inhibits the formation of network carbides, promotes the phase transformation of high-temperature austenite to sorbite, and forms a structure dominated by sorbite with fine lamellar spacing. After that, the wire rod is conveyed by a roller through the second stage salt bath tank The post-stage treatment is carried out, and the molten salt circulation volume of the post-stage treatment is appropriately reduced to reduce production energy consumption, further control the stress relief of the wire rod in the high-temperature isothermal zone, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature is 525°C, and the total treatment time is 230s, of which the molten salt circulation volume of the front-stage treatment is 350t / h, the molten salt temperature rise is ≤10°C, and the treatment time is 220s; the molten salt circulation volume of the post-stage treatment is 180t / h, the molten salt temperature rise is ≤5°C, and the treatment time is 10s.
[0051] The roller slow cooling process adopts closing the heat preservation cover, and the wire rod passing through the second salt bath tank is transported by the conveyor roller into the heat preservation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to be slowly cooled to 270°C at a cooling rate of 0.3°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0052] Comparative Example 3:
[0053] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which differs from that of Example 2 in that: when the wire rod undergoes front-end processing, the wire rod is cooled at a cooling rate of 34°C / s, the molten salt temperature is 565°C, and a hot-rolled wire rod finished product is obtained after it comes off the line.
[0054] Comparative Example 4:
[0055] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which differs from that of Example 2 in that: when the wire rod undergoes front-end treatment, the wire rod is cooled at a cooling rate of 40°C / s, the molten salt temperature is 475°C, and a hot-rolled wire rod finished product is obtained after it comes off the line. Embodiment 3:
[0056] A preferred embodiment of the manufacturing method of the 2100MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.91%, Si: 1.30%, Mn: 1.2%, Cr: 0.53%, P: 0.013%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt sorbentization control treatment → roller slow cooling → coiling, specifically:
[0057] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, and reduce segregation. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 15.5mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process, and specifically: control the heating furnace soaking temperature to 1200°C, and the furnace time to 1 80min, the initial rolling temperature is 1160℃, the final rolling temperature is 1020℃, and the final rolling reduction is 22%; the wire-spinning process is used to make the wire rods out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to promote the wire rods to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the troostite phase transformation dominated by fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 985℃.
[0058] The online molten salt sorbitization control treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region, inhibits the formation of network carbides, promotes the phase transformation of high-temperature austenite to sorbite, and forms a structure dominated by sorbite with fine lamellar spacing. After that, the wire rod is conveyed by a roller through the second stage salt bath tank The post-stage treatment is carried out, and the molten salt circulation volume of the post-stage treatment is appropriately reduced to reduce production energy consumption, further control the stress relief of the wire rod in the high-temperature isothermal zone, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature is 511°C, and the total treatment time is 280s, of which the molten salt circulation volume of the front-stage treatment is 420t / h, the molten salt temperature rise is ≤10°C, and the treatment time is 195s; the molten salt circulation volume of the post-stage treatment is 220t / h, the molten salt temperature rise is ≤5°C, and the treatment time is 85s.
[0059] The roller slow cooling process adopts closing the insulation cover, passing the hot air above the salt bath tank into the insulation cover, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 286°C at a cooling rate of 0.2°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain a hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0060] Comparative Example 5:
[0061] A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the total processing time of the online molten salt sorbitization regulation treatment is 140s, of which the processing time of the front-end treatment is 125s and the processing time of the back-end treatment is 15s, and the hot-rolled wire rod finished product is obtained after going offline.
[0062] Comparative Example 6:
[0063] A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the total processing time of the online molten salt sorbitization regulation treatment is 450s, of which the processing time of the front-end treatment is 300s and the processing time of the back-end treatment is 150s, and the hot-rolled wire rod finished product is obtained after going offline. Embodiment 4:
[0064] A preferred embodiment of the manufacturing method of the 2100MPa grade hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.9%, Si: 1.10%, Mn: 1.05%, Cr: 0.67%, P: 0.015%, S: 0.013%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt sorbentization control treatment → roller slow cooling → coiling, specifically:
[0065] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote uniform diffusion of components in the steel billet, and reduce segregation. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 14mm through a rolling line, and a suitable rolling temperature and deformation amount are selected to improve the rolling speed and efficiency, promote dynamic recrystallization and refine grains during the final rolling process, and specifically: control the heating furnace soaking temperature to 1180°C, the furnace time to 19 0min, the initial rolling temperature is 1145℃, the final rolling temperature is 1000℃, and the final rolling reduction is 23%; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. A higher wire-spinning temperature is selected to promote the wire rod to be in a high-temperature austenite state, and to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to form a larger temperature gradient later, which provides favorable conditions for promoting the troostite phase transformation dominated by fine lamellar spacing. Specifically, the wire-spinning temperature is controlled to be 970℃.
[0066] The online molten salt sorbitization control treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to the sorbite phase region, inhibits the formation of network carbides, promotes the phase transformation of high-temperature austenite to sorbite, and forms a structure dominated by sorbite with fine lamellar spacing. After that, the wire rod is conveyed by a roller through the second stage salt bath tank The post-stage treatment is carried out, and the molten salt circulation volume of the post-stage treatment is appropriately reduced to reduce production energy consumption, further control the stress relief of the wire rod in the high-temperature isothermal zone, and improve the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature is 490°C, and the total treatment time is 185s, of which the molten salt circulation volume of the front-stage treatment is 400t / h, the molten salt temperature rise is ≤10°C, and the treatment time is 160s; the molten salt circulation volume of the post-stage treatment is 250t / h, the molten salt temperature rise is ≤5°C, and the treatment time is 25s.
[0067] The roller slow cooling process adopts closing the insulation cover, passing the hot air above the salt bath tank into the insulation cover, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover to prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 295°C at a cooling rate of 0.1°C / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0068] Comparative Example 7:
[0069] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to the process flow of rolling → spinning → online molten salt sorbitization control treatment → air cooling → coiling, and the air cooling process adopts opening the insulation cover to control the wire rod to be cooled to 290°C at a cooling rate of 1.1°C / s, and the hot-rolled wire rod finished product is obtained after it comes off the line.
[0070] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below:
[0071] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods
[0072]
[0073] It can be seen from the comparison results of Example 1 and Comparative Example 1 that compared with the design with high Si-Mn chemical composition, the strengthening effect is often weakened due to the uncontrollable cooling rate during the cooling phase transformation process of the Stelmor air-cooled line, and abnormal structures such as network carbides and martensite are generated, which limits the rapid phase transformation of troostite. The proportion of soft phase ferrite is relatively large, making the obtained hot-rolled wire rod insufficient in strength and plasticity, difficult to stably produce, and high in the risk of wire breakage during the wire drawing process. The present invention combines the online molten salt troostitization control technology to effectively control the production process. The network carbide, martensite and other deteriorated structures in the wire rod are removed, and the microstructure type is a mixed structure composed of tempered troostite, ferrite and fused troostite, which can improve the strengthening effect of carbon elements and alloy elements, and thus improve the overall strength and plasticity of the wire rod. It can be seen from the results of Examples 1 to 4 that the product tensile strength can reach 1500 to 1540 MPa, and the cross-sectional shrinkage rate is 37% to 42%. It is used to manufacture 2100 MPa ultra-high strength bridge cables and other application fields, which is conducive to meeting the requirements of drawing, hot-dip galvanizing and torsion performance.
[0074] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the use of a higher spinning temperature can avoid the precipitation of cementite and the formation of network carbides during the spinning stage caused by the spinning temperature being too low, and at the same time provide favorable conditions for promoting the nucleation and refinement of troostite.
[0075] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the higher the molten salt temperature of the online molten salt troostitizing regulation treatment, the more thermal power can be provided, which is beneficial to promoting the toughening of the wire rod structure and improving the softening effect. However, if the molten salt temperature is too high, it is not conducive to promoting the troostite phase transformation of the fine lamellar spacing, which will result in strength loss.
[0076] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the lower the molten salt temperature of the online molten salt troostitizing regulation treatment, the greater the degree of supercooling can be formed, which is beneficial to promoting the transformation of austenite to troostite and controlling the refinement of cementite lamellae, and can improve the matrix strength. However, if the molten salt temperature is too low, it is not conducive to controlling the rapid isothermal stress relief of the wire rod, which will cause plasticity loss.
[0077] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the shorter the treatment time of the online molten salt troostitizing regulation treatment, the lower the toughening and softening effect of the wire rod structure will be. However, if the treatment time is too short, the stress of the wire rod structure will be high, which will lead to insufficient plasticity, and even the wire rod will not be fully transformed into troostite, which will cause strength loss.
[0078] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the longer the treatment time of the online molten salt troostitizing regulation treatment is, the more it can promote the full transformation of austenite to troostite and reduce the ferrite content. At the same time, it can make the wire rod stress-relieved in a longer high-temperature isothermal zone and regulate the strength and plasticity of the wire rod. However, if the treatment time is too long, the melting of troostite will increase, which will bring a certain strength loss. The precipitation and coarsening of Cr at high temperature for a long time is not conducive to the strength and plasticity.
[0079] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the use of roller slow cooling can prevent the wire rod from cooling too fast during the cooling process, resulting in increased stress, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod.
[0080] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 2100MPa grade hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.88%~0.92%, Si: 1.10%~1.30%, Mn: 1.00%~1.20%, Cr: 0.47%~0.67%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥955°C, it is subjected to an online molten salt sorbitization control treatment so that the wire rod is spun at a spinning temperature of ≥36°C / s The temperature is reduced at a cooling rate from the austenite state into the sorbite phase region, the sorbite phase transformation is promoted and the stress is relieved by isothermal treatment, and finally the wire rod is slowly cooled by a roller to be made into a hot-rolled wire rod with a microstructure including tempered sorbite with a volume percentage of ≥95% and the rest being a mixed structure composed of ferrite and fused sorbite; the molten salt temperature of the online molten salt sorbitization control treatment is 490-525°C, the treatment time is 170-360s, and the roller slow cooling controls the wire rod to be slowly cooled to below 300°C at a cooling rate of 0.1-0.3°C / s.
2. The method for manufacturing the 2100MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the heating furnace is controlled to have a soaking temperature of 1150-1200° C. and the time in the furnace is ≥180 min.
3. The method for manufacturing the 2100MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1120-1160° C., the final rolling temperature is controlled to be 980-1020° C., and the final rolling reduction is controlled to be 22%-27%.
4. The method for manufacturing the 2100MPa grade hot rolled wire rod for bridge cables according to claim 1, characterized in that: The online molten salt troostitization regulation treatment is divided into front-end treatment and back-end treatment; the molten salt circulation volume of the front-end treatment is 350-420 t / h, the molten salt temperature rise is ≤10°C, and the treatment time is 160-260s; the molten salt circulation volume of the back-end treatment is 150-250 t / h, the molten salt temperature rise is ≤5°C, and the treatment time is 10-100s.
5. A 2100MPa grade hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 2100MPa-grade hot-rolled wire rod for bridge cables according to any one of claims 1 to 4.
6. The 2100MPa grade hot rolled wire rod for bridge cables according to claim 5, characterized in that: The interlamellar spacing of the tempered troostite is 65-115 mm.
7. The 2100MPa grade hot rolled wire rod for bridge cables according to claim 5, characterized in that: The network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is less than 60 MPa.
8. The 2100MPa grade hot-rolled wire rod for bridge cables according to claim 5, characterized in that: The hot-rolled wire rod has a diameter of 12.0-15.5 mm, a tensile strength of 1500-1540 MPa, and a cross-sectional shrinkage of 37%-42%.
Citation Information
Patent Citations
A steel for bridge cables with a tensile strength ≥2100MPa and its production method
CN107587071B
Wire rod for high-strength bridge cable and production method of wire rod
CN118880169A
Hot-rolled wire rod for 1860MPa bridge cable and manufacturing method of hot-rolled wire rod
CN119040751A